PERTANGGUNGJAWABAN SEKUTU DALAM PERSEKUTUAN KOMANDITER YANG MENGALAMI KEPAILITAN - Diana Safitri, Novita; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
In the company there are two forms of legal business entity, a business entity that is not a legal entity and incorporated business entities. Limited partnership is considered as a non-legal entity form the company. There are two forms of partnership in limited partnership; they shall be the limited partnership and complementary partnership. A limited partnership form does not simply waive the possibility of bankruptcy. The purpose of this paper is to examine means of responsibility upon the circumstances of bankruptcy in limited partnership. This paper shall utilize normative legal research, where it shall conceptualize law as the enunciation of acts. Bankruptcy of limited partnership means the bankruptcy of the partner, not simply the partnership. Partner shall be liable to its respected limited bonds. In the matter of bankruptcy by limited partnership, complementary partner shall be held responsible due to its position as the managing roles of the partnership. Limited partnership responsibilities shall only lie upon the capital invested.
Keywords: Liability, Limited Partnership, Partner, Bankruptcy